Religiosity and Local Wisdom in Teaching Cultural Science in Faculty of Languages and Arts of Semarang State University - sunahrowi sunahrowi; Anastasia P; Singgih K (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
Teaching Cultural Science in the Faculty of Languages and Arts of Semarang State University has conducted for 8 years. This course is estimated to have been studied by 10 thousands of students, assuming that every in year, there are 1200 new students in the Faculty of Languages and Arts. The amount of students and the demands of the significant role on the existence of subject’s Cultural science in the formation of Indonesian human characters encourage the teachers and writers of this subject matter to innovate to meet the demands. The selection of themes on religiosity, local wisdom, the use of appropriate methods, contextual teaching and learning method, becomes a crucial necessity. Based on this research, the need for teaching materials with the theme of religious activities and local wisdom is needed by the students to implement theoretical studies in this course. The selection of appropriate methods, contextual teaching and learning method, is also a need to apply the main theories and themes in teaching cultural science, among others; cultural studies, cultural structuralism, postmodernism, feminism, and orientalism.